Getting personal: A feminist argument for research aligned to therapeutic practice. Issue 2 (10th February 2017) - Bondi, Liz; Fewell, Judith
Abstract: Students and practitioners tend to assume that research requires them to set aside their embodied knowledge of practice and to produce radically different, objective and depersonalised forms of knowledge. Troubled by these assumptions, and coming from backgrounds within the humanities and social sciences shaped by critiques of this model of research, we offer personal stories through which to articulate and argue for a very different approach. Feminist critiques of science occupy a central place within our stories, which tell of the pull of the particular, the personal and the subjective, the importance of personally engaged, reflexive stories, and the influence of moving between disciplines. We understand the personal in research as inevitable, contextually located and deeply relational.